Efisiensi Teknis Usaha Tani Padi di Provinsi Kepulauan Bangka Belitung - Fitri Kartiasih; Adi Setiawan (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2019)
Rice productivity in Indonesia varied greatly between provinces. Rice productivity in the Bangka Belitung Islands was the lowest figure compared to other provinces in Indonesia from 2013 to 2015. The purpose of this study was to provide an overview of rice farming, analyze the technical efficiency and its influencing factors of rice farming, and analyze the income level of rice farming in the Province of Bangka Belitung Islands. The data used in this study were raw data of the 2014 Household Survey of Rice Crop Farming (SPD 2014) conducted by Statistics Indonesia. The analytical method used was the Stochastic Production Frontier. The results showed that the factors influencing rice production were seeds, fertilizers, pesticides and the use of hired labours. The average level of technical efficiency of rice farmers was 20% of maximum production. This shows that rice farming was not yet efficient. Factors that negatively affect the technical efficiency of rice farming were those among other age of the farmer, land preparation equipment, ownership status of land preparation equipment and the planting system. The results of the study also showed that the more efficient the rice farming, the greater the farmers' income. To increase productivity through increasing technical efficiency, it is recommended that rice farmers are facilitated or supported to use a better quality of rice seed. AbstrakProduktivitas padi di Indonesia sangat bervariasi antar provinsi, di mana produktivitas padi di Kepulauan Bangka Belitung menunjukkan angka terendah dibandingkan provinsi lain di Indonesia selama tahun 2013 hingga 2015. Tujuan penelitian ini antara lain untuk memberikan gambaran usaha tani padi di Provinsi Kepulauan Bangka Belitung, menganalisis efisiensi teknis usaha tani padi serta faktor-faktor yang memengaruhinya, dan menganalisis tingkat pendapatan usaha tani padi. Data yang digunakan dalam penelitian ini adalah raw data hasil Survei Rumah Tangga Usaha Tanaman Padi 2014 (SPD 2014). Metode analisis yang digunakan adalah Stochastic Production Frontier. Berdasarkan hasil penelitian menunjukkan bahwa faktor-faktor yang memengaruhi produksi padi di Kepulauan Bangka Belitung adalah penggunaan benih, pupuk, pestisida dan penggunaan pekerja dibayar. Rata-rata tingkat efisiensi teknis petani padi di Kepulauan Bangka Belitung adalah 20% dari produksi maksimum. Hal ini menunjukkan bahwa usaha tani padi belum efisien. Faktor-faktor yang berpengaruh negatif terhadap infesiensi teknis usaha tani padi adalah faktor umur petani, alat pengolahan lahan, status alat pengolahan lahan dan sistem tanam. Hasil penelitian juga menunjukkan bahwa semakin efisien usaha tani padi maka pendapatan petani juga semakin besar. Untuk meningkatkan produktivitas dengan cara meningkatkan efisiensi teknis, disarankan petani padi difasilitasi atau didorong untuk menggunakan benih yang berkualitas.